LEONARDO DIGITALE, APPLICAZIONI VIRTUALI PER IL CINQUECENTENARIO LEONARDIANO ALLA MOSTRA "LEONARDO E VITRUVIO. OLTRE IL CERCHIO E IL QUADRATO.” - Clini, Paolo; Angeloni, Renato; D'Alessio, Mirco; Buroni, Paolo; Buroni, Alex (Archeomatica, 2020)
The development of tools for digital representation and the diffusion of media to display it offer an effective mean for the creation and dissemination of cultural contents. This article presents a research work for the exhibition "Leonardo e Vitruvio. Oltre il cerchio e il quadrato.” hosted in the city of Fano for the celebration of the 500th anniversary of Leonardo's death. Starting from the original drawings exposed, Leonardo's crossbow, odometer and water clock were 3D modelled reproducing up to the smallest component and virtually simulating their exact functioning. Hence, two different applications were developed using these digital reconstruction to support visitors. They explain the represented machines from conception to use and compare Leonardo's models with those of the past, making possible a dynamic fruition that goes beyond the passive experience of contemplating the original work of art.